2002
DOI: 10.1007/s005950200062
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial Lipoma Accompanied with Primary Lung Cancer: Report of a Case

Abstract: A 72-year-old man was found to have an endobronchial lipoma accompanied with primary lung cancer. A left lower lobectomy with a mediastinal lymph node dissection and a sleeve resection of the lingual bronchus with telescoping bronchial anastomosis were done. The pathological staging was T1N2M0, stage IIIA. A histological examination showed well-differentiated squamous cell carcinoma in segment 10, in addition to the presence of mature adipose tissue which was diagnosed to be a benign endobronchial lipoma origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…A new type of diaphragmatic hernia: Anterolateral hernia JØrôme Mouroux, MD, PhD, Daniel Pop, MD, Patrice Guiraudet, MD, Ricardo Giovanetti, MD, JØrôme Lauron, MD, and Nicolas Venissac, MD, Nice, France H eterogenous types of acquired hernias in the diaphragm have been described in the literature: the hiatal hernia through the esophageal foramen and the posterolateral hernia through the Henle costolumbar orifice or anterior foramen of Larrey-Morgagni hernia (retroxiphoid hernias). 1,2 To our knowledge, no anterolateral hernia has been reported. We describe the case of a hernia between the eighth and ninth anterior costochondral insertion of the muscular fibers of the diaphragm.…”
Section: Clinical Summarymentioning
confidence: 83%
See 2 more Smart Citations
“…A new type of diaphragmatic hernia: Anterolateral hernia JØrôme Mouroux, MD, PhD, Daniel Pop, MD, Patrice Guiraudet, MD, Ricardo Giovanetti, MD, JØrôme Lauron, MD, and Nicolas Venissac, MD, Nice, France H eterogenous types of acquired hernias in the diaphragm have been described in the literature: the hiatal hernia through the esophageal foramen and the posterolateral hernia through the Henle costolumbar orifice or anterior foramen of Larrey-Morgagni hernia (retroxiphoid hernias). 1,2 To our knowledge, no anterolateral hernia has been reported. We describe the case of a hernia between the eighth and ninth anterior costochondral insertion of the muscular fibers of the diaphragm.…”
Section: Clinical Summarymentioning
confidence: 83%
“…Almost two thirds of the tumors occur in the right side, and they are usually located in the main-stem or lobar bronchi. [1][2][3] Smoking and obesity are significant risk factors for EL development. 4 Cough, hemoptysis, and shortness of breath are common symptoms, 4,5 and patients are often misdiagnosed and treated for asthma for many years, as was our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 8 Endobronchial lipomas occur predominately in men aged 50–80 years old, but rarely in women. 1 5 , 7 10 Clinical symptoms in the vast majority of patients include cough, expectoration, hemoptysis, asthma, fever, and dyspnea, but there is no typical symptom. 1 , 9 , 10 It is well known that smoking and obesity are risk factors, but neither of these factors is found in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…(8)(9) In some cases, there might be concomitant neoplastic disease, principally primary pulmonary tumor. (10) In a recent review of the Japanese literature, it was shown that 64 cases of endobronchial lipoma were reported between 1971 and 2001, accounting for 0.1% to 0.5% of all pulmonary tumors. (11) In the search for endobronchial lesions of adipose origin, chest X-rays are nonspecific.…”
Section: Discussionmentioning
confidence: 99%